Fizicheskoe vospitanie v Pol'skikh vyscikh shkolakh - Voinar, J. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The purpose of this paper was the historical analysis the historical analysis of physical education's development in Polish highest schools. The author has made an attempt of historical periodicity of this process: The first stage - before the first world war; The second stage - intermilitary twenty years; The third stage - after the Second World War and until the present time.